STUDI PENGGUNAAN LIMBAH PLASTIK PADA PEMBUATAN DINDING PARTISI DENGAN PENAMBAHAN SERAT ROVING - Nur Aisyah Jalali; Khairil; Irka Tangke Datu; Aldi Massa; Afdil Prayudia Aspi, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Indonesia produced many of waste, of which 60% was successfully managed, while the rest piled up in landfills. About 17% of waste was plastic that is difficult to decompose, which prompted us to conduct research. The aim of the research was to determine the flexural strength of partition walls without additions and with the addition of Roving fibers. Partition walls were made from PCC type Portland cement, fine aggregate (sand), coarse aggregate (plastic pellets) from LDPE type plastic waste, Roving fiber, and water, while Curing Compound Antisol E-125 was used for maintenance. The specimen consisted of cylinder diameter 10 cm height 20 cm, partition walls 75x25x3 cm without addition and with the addition of Roving fiber (0.5% and 1% of the fiber density). Testing showed that all specimens were structural lightweight concrete with a bulk density of 1400-1850 kg/m3. Flexural strength test results showed that without the addition of fiber was 2.36 MPa, with the addition of 0.5% and 1% fiber were 2.05 MPa and 2.21 MPa. In conclusion, the flexural strength were almost the same, so it was not recommended